2013
DOI: 10.1186/1743-8977-10-23
|View full text |Cite
|
Sign up to set email alerts
|

Comparative inhalation toxicity of multi-wall carbon nanotubes, graphene, graphite nanoplatelets and low surface carbon black

Abstract: BackgroundCarbon nanotubes, graphene, graphite nanoplatelets and carbon black are seemingly chemically identical carbon-based nano-materials with broad technological applications. Carbon nanotubes and carbon black possess different inhalation toxicities, whereas little is known about graphene and graphite nanoplatelets.MethodsIn order to compare the inhalation toxicity of the mentioned carbon-based nanomaterials, male Wistar rats were exposed head-nose to atmospheres of the respective materials for 6 hours per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
120
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(130 citation statements)
references
References 48 publications
(48 reference statements)
9
120
1
Order By: Relevance
“…For example, in vivo studies are often carried out with lower doses per lung surface (excluding overload experiments). For various carbonaceous materials, it has been demonstrated that at similar doses, carbon black and graphite have no effect (0.1 or 0.03 µg/cm 2 , respectively; an estimate of the rat lung surface area 0.3 m 2 was used in this calculation (Brown et al, 2005)), but graphene and multiwall carbon nanotubes do have an effect (0.03 or 0.01 µg/cm 2 , respectively (Ma-Hock et al, 2013)). Moreover, in vivo investigations have shown that both the dosing rate and the delivered dose are responsible for toxicological effects.…”
Section: Tab 3: System Specifications For the Mts Assay As Defined Bmentioning
confidence: 99%
“…For example, in vivo studies are often carried out with lower doses per lung surface (excluding overload experiments). For various carbonaceous materials, it has been demonstrated that at similar doses, carbon black and graphite have no effect (0.1 or 0.03 µg/cm 2 , respectively; an estimate of the rat lung surface area 0.3 m 2 was used in this calculation (Brown et al, 2005)), but graphene and multiwall carbon nanotubes do have an effect (0.03 or 0.01 µg/cm 2 , respectively (Ma-Hock et al, 2013)). Moreover, in vivo investigations have shown that both the dosing rate and the delivered dose are responsible for toxicological effects.…”
Section: Tab 3: System Specifications For the Mts Assay As Defined Bmentioning
confidence: 99%
“…Levels of statistical significance: *p 0.05 and **p 0.01 compared to appropriate control group. between the 'synthetic' and 'biological' identities of nanoparticle formulations and observed in vivo effects (Ma-Hock et al, 2013). Lastly, human exposure to nanoparticles rarely, if ever, occurs to well-defined nanoparticle preparations.…”
Section: Discussionmentioning
confidence: 99%
“…The toxicity of MWCNTs is more adverse in the case of inhalation as compared to oral exposure. Rats exposed to 2.5 mg/m 3 MWCNTs for 6 h/day during 5 consecutive days using a head-nose system demonstrated signs of pulmonary toxicity such as, microgranulomas and diffuse alveolar histiocytosis (Ma-Hock et al, 2013). After a 13-week exposure period, the inhalation of 2.5 mg/m 3 MWCNTs induced systemic inflammation and histopathological abnormalities in the lungs, lymph nodes, nasal cavity, larynx, and trachea (Ma-Hock et al, 2009).…”
Section: Mammalian Toxicity (Rodents)mentioning
confidence: 99%